BMI-NECK: A simple assessment of risk of obstructive sleep apnea in schizophrenia. (June 2020) - Szaulińska, Katarzyna; Wichniak, Adam
Abstract: Introduction: A high risk of obstructive sleep apnea (OSA) has been reported in patients with schizophrenia. However, existing screening questionnaires for OSA haven't been validated in this population and the impact of OSA on schizophrenia symptoms has rarely been studied. This study aimed to investigate the prevalence and impact of OSA in patients with schizophrenia and validate the existing OSA screening scales. Method: Patients with schizophrenia consecutively admitted to hospital ( n  = 51) and patients with schizophrenia and obesity ( n  = 31) were compared to healthy controls ( n  = 51). Apnea risk was measured with STOP-BANG, NoSAS, No-Apnea, and the Berlin Questionnaire; psychiatric symptoms were measured with the PANSS and Calgary scales and B-CATS battery. Daytime sleepiness was measured with the Epworth sleepiness scale. OSA was diagnosed using the Embletta system. Results: OSA was found more frequently in obese schizophrenia patients than in those consecutively admitted to hospital (45% vs. 22%, p  < 0.05). Significant differences between patients with and without OSA were found on the PANSS negative symptoms subscale, B-CATS digit symbol test, and in daytime sleepiness. None of the used screening scales showed satisfactory sensitivity and specificity. Obesity with coexisting neck circumference ≥41 cm in women or ≥43 cm in men (BMI-NECK model) predicted OSA in 57% of cases. Conclusions: OSA should be screened in patients with schizophrenia as it has a negative influence on psychiatric symptoms and may contribute to the higher mortality of these patients. Assessment of BMI and neck circumference proves a good screening test in ambulatory contexts.